The Liability of European States for Climate Change - Cox, Roger H J (Utrecht Journal of International and European Law, 2014)
According to climate science and the 195 signatory States to the UN Climate Convention, every emission of anthropogenic greenhouse gases contributes to climate change. Furthermore, they hold that a two degree Celsius rise of Earth’s average temperature is to be considered as a dangerous climate change to mankind and all of the world’s ecosystems. Using the climate proceedings of Dutch citizens against the Dutch state as a starting point, the author of this case note explains why each European Member State’s contribution to dangerous climate change as a result of inadequate emission reduction policies constitutes a tort of negligence against its citizens and poses a real threat for its citizens’ effective enjoyment of human rights. The author argues that this makes individual European Nations severally liable for dangerous climate change and gives European citizens and non-governmental organisations the possibility to request their Nation State’s competent court to compel the Nation’s government to implement stricter emission reductions in accordance with what is deemed necessary to help avoid dangerous climate change and to protect their human rights.